The formative periods of Indian thought: Non-essentialist notes - Wulff Alonso, Fernando (2025)
The origins and consequences of four essentialist aspects of the “Vedic-Hindu” world picture in antiquity are analyzed: 1. Organic and unbroken evolution. 2. Hegemony. 3. An evolution without contact or participation in common components with other religious currents. 4. Isolation from the outside of the Subcontinent.